Tourism as a dementia treatment based on positive psychology. (October 2022) - Wen, Jun; Zheng, Danni; Hou, Haifeng; Phau, Ian; Wang, Wei
Abstract: No research in tourism or medicine has addressed the potential relationship between travel and the medical treatment of dementia. Given tourism's increasingly important role in society, a cross-disciplinary team of tourism and dementia experts provide insight into the potential benefits of tourism for individuals with dementia. This conceptual effort critically reviews the tourism and dementia literature and addresses pertinent knowledge gaps. Tourism is presented as a possible way to improve dementia patients' well-being as an adjunct to non-pharmacological interventions. Accordingly, a conceptual framework is proposed to highlight the nexus between tourism experiences and dementia interventions. Future interdisciplinary research directions are also described. Graphical abstract: Image 1